Pengaruh Konservatisme Akuntansi dan Good Corporate Governance Terhadap Manajemen Laba - Ma'rifah, Fitriani; Suwarno, Suwarno (Journal of Culture Accounting and Auditing, 2025)
This research aims to examine the influence of accounting conservatism and Good Corporate Governance as a proxy for institutional ownership, independent commissioners and managerial ownership on earnings management. The sample selection in this study used a purposive sampling method from manufacturing companies listed on the Indonesian Stock Exchange (IDX) in 2020-2021. The sample for this research was 81 companies. In this study, SmartPLS 4.0.9.4 software was used. The PLS test results of this research show that accounting conservatism has a significant effect on earnings management, while Good Corporate Governance as a proxy for institutional ownership, independent commissioners and managerial ownership has no effect on earnings management.